O gênero discursivo homilia: intertextualidade e dialogia nas práticas religiosas católicas - PINTO, Juliana de Sousa (2011)
This work now presented emerged from the professional and personal anxieties, from the actuation in a project developed by the Núcleo de Estudos, Pesquisa e Extensão em Agricultura Familiar NEAF/UFG, in the Rio Claro (P.A.) Projeto de Assentamento in Jataí, State of Goiás. And has as the objective, to analyze the social and spatial trajectory of the families from this setting, besides to verify the influence of these trajectories in the present time of their lives, as seat people. So some specific objectives were established, just as to analyze the social and spatial trajectory of the families from the Rio Claro P.A. in the previous phases to the constitution of this setting: the previous phase to the land battle; to understand how the constitution of the P.A. was realized, and to verify which were the influences of the social and spatial trajectories of the families in the social and productive organization of the setting. These trajectories were divided in three phases, the previous phase to the entering into the land battle, which gives the basis for the first part of the work; the phase of the battle for land, which gives basis the second part; and finally the present phase of their social and spatial trajectories, as seat people, constituting the third part. According to these objectives, we took bold of the following methodological instruments which permitted the development of this study: bibliographic and documental research through the data supplied by the Sindicato dos Trabalhadores Rurais de Jataí (Jataí Rural Labor Union) and the DATALUTA data bank, which permitted the secondary data collection; field research, with the use , as instruments of data collection, of a form with closed and open questions and a semi organized interview, which propitiated the collection of the primary data. In the form we obtained the participation of 17 families who compose the Rio Claro setting, in a total of 19 people. 10 families participated in the interview, totalizing 13 researched people. After realizing this study it was possible to conclude that, to research the social and spatial trajectories from the components of the P.A. Rio Claro was fundamental to understand the social and productive relationships established in the setting and among people of the researched group, being possible to indentify the origins of the families, the cause they were expropriated from the land, and how they entered into the movement of the land battle and how they created the setting which nowadays guarantees them the production of their ways of life, through the work in the conquered peace of land .